PROSPEK BRIKET BATUBARA LIGNIT SEBAGAI BAHAN BAKAR ALTERNATIF SEKTOR RUMAH TANGGA DAN INDUSTRI KECIL - Rahardjo, Bambang Suwondo; Yusniati, Yusniati (Badan Pengkajian dan Penerapan Teknologi, 2007)
Market coal briquette compartment in Indonesia is estimated still big enough,considering kerosene and firewood which was usually used as small industrialand rural household sector fuel progressively scarce and costly if without subsidy.Coal briquette of lignit made of low rank coal without carbonization process and without binder, so that can become alternative fuel which is competitif, safe, efficient and environmental friendliness. Volatile matter content can be decreased by using special design of stove to burn it by fire tongue on the surface of stove to yield completely combustion. Continueing usage of coal briquette as alternative fuel substitution of kerosene and or firewood especially in rural, can be conducted by given system and sustanable supply guarantee, quality improvement, economical charcoal burner device of the environmental friendly, efficiently and routine promotion activities.